Measuring Adult Drivers' Use of Level 1 and 2 Driving Automation by Roadway Functional Class. (November 2019) - Reagan, Ian J.; Hu, Wen; Cicchino, Jessica B.; Seppelt, Bobbie; Fridman, Lex; Glazer, Michael
Little is known about the use of driving automation in production vehicles. This study measured mileage driven on different roadway classes when level 1 and 2 automation was engaged. Volunteer drivers drove for 4 weeks in a Range Rover Evoque with adaptive cruise control (ACC) or a Volvo S90 with ACC and Pilot Assist (PA) with one of two versions of PA software. The highest percentage of mileage driven when the automation was on/active (39.5%) was on interstates, other freeways, and expressways. The Evoque's ACC was engaged for a higher percentage of miles than the S90's ACC or PA. The S90's software change was associated with a doubling of mileage driven on interstates, other freeways, and expressways when PA was on/active. The study identified potential misuse with some drivers engaging automation for relatively high percentages of mileage on road classes where owner manuals indicate use may be inappropriate.